Teknik Behavior dalam Menangani Perilaku Indisipliner Siswa pada Korban Perceraian di SMP Diponegoro Sleman Yogyakarta - Muchamad Agus Slamet wahyudi (Cendekia: Kependidikan dan Kemasyarakatan, 2017)
This study examined behavioral approach in dealing with students’ indiscipline behavior at SMP Diponegoro Depok Sleman Yogyakarta whose family background of divorce. Qualitative descriptive methodwas applied to reveal the above phenomenon and the data were collected by observation and in-depth interview. It revealed that there were three main steps in applying this behavior approach. Firstly, assessment was essentially conducted in advance to investigate the underlying factors which cause indiscipline to happen. The second step was a goal setting; discussing with students about the consequences that might be faced when they engage in undisciplined behavior. At this stage, the researcher along with the students had succeeded in devising a plan to solve the problem. The last stage was that carrying out the research to assess students followed by counseling contract, relaxation, modeling, reward and punishment, encouragement, time-out, home assignment and ending with the evaluation phase. The results found that behavioral technique was one of effective approaches in guidance and counseling to handle maladaptive on adaptive behavior, and this approach was very appropriate to handle undisciplined students in school.  درس هذا البحث عميقا عن المدخل السلوكي في معالجة ظاهرة "اللا انضباط"  لدى طلاب المدرسة المتوسطة العامة ديفونيغورو ديفوك سيليمان يوغياكرتا بخلفية فراق الوالدين.  ولكشف هذه الظاهرة، استخدم هذا البحث منهج البحث الوصفي الكيفي. وجُمعت البيانات عن طريق الملاحظة والمقابلة الشخصية. وحصل الباحث على نتائج البحث، وهي ثمة ثلاث خطوات رئيسية في تطبيق المدخل السلوكي، وهي أولا : التقييم، وهو عملية أولية للكشف عن خلفية سلوك "اللا انضباط"   ، ثانيا : إثبات الأهداف، وهو المناقشة مع الطلاب عن  الهمجيّة الذي يواجهها الطلاب إذا مارسوا سلوك "اللا انضباط"  . في هذه المرحلة استطاع الباحث مع الطلاب وضع خطة لحل المشاكل.  ثالثا :  إن تطبيق هذا البحث من البداية، هو إجراء التقييم تجاه الطلاب ثم عقد المشورة، والاسترخاء، والتصميم، التكريم والعقاب، والتقوية، ونفذ الوقت، والواجب المنزلي، وفي الأخير التقويم. بهذا يكون الأسلوب السلوكي أحد المداخل في التوعية والإرشاد لمعالجة عدم قدرة الطالب على التكيّف، وهذا الأسلوب ناجع ومناسب لعلاج سلوك اللاانضباط الواقع عند الطلاب في المدرسة.